ELMO1 protects renal structure and ultrafiltration in kidney development and under diabetic conditions - Sharma, Krishna Rakesh; Heckler, Karl; Cramer-Stoll, Sandra; Kynast, Katharina; Herpel, Esther; Porubský, Štefan; Elger, Marlies; Hadaschik, Boris; Bieback, Karen; Hammes, Hans-Peter; Nawroth, Peter Paul; Kroll, Jens (Scientific reports, 2016)
Engulfment and cell motility 1 (ELMO1) functions as a guanine exchange factor for Rac1 and was recently found to protect endothelial cells from apoptosis.
Gesehen am 17.01.2017